1977
DOI: 10.1055/s-0028-1097617
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Investigation of Wild Cannabis Sativa L. Roots

Abstract: Petrol and benzene extracts of the mature plant roots have led to the isolation of five compounds which have been characterised as friedelin, epifriedelinol, ,6-sitosterol, carvone and dihydrocarvone. In case of latter two compounds, GLC studies were carried to establish their identity. In addition to these compounds, the chloroform extract of the ammoniacal water treated roots have led to the isolation of some basic constituents which respond to the alkaloidal tests. Due to very low concentration of these bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“… 60 Future research should compare the phytochemistry of hemp roots with those from various drug chemovars to determine if there are differences in active compounds. Furthermore, reports of carvone and dihydrocarvone in significant amounts 20 and other potential monoterpenes in cannabis roots must be confirmed. Modern studies using the same terpenoids found in cannabis roots have shown anti-inflammatory and pain-relieving activities.…”
Section: Summary and Future Directionsmentioning
confidence: 98%
See 3 more Smart Citations
“… 60 Future research should compare the phytochemistry of hemp roots with those from various drug chemovars to determine if there are differences in active compounds. Furthermore, reports of carvone and dihydrocarvone in significant amounts 20 and other potential monoterpenes in cannabis roots must be confirmed. Modern studies using the same terpenoids found in cannabis roots have shown anti-inflammatory and pain-relieving activities.…”
Section: Summary and Future Directionsmentioning
confidence: 98%
“…Sethi et al 20 collected wild cannabis roots from Jammy, India. From an initial 2 kg sample of dried powdered roots, the extraction assay revealed 15 mg of friedelin, 29 mg epifriedelanol, and 30 mg of beta-sitosterol.…”
Section: Active Compounds In Cannabis Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cannabis roots have proven to harbor terpenoids, sterols [106], and alkaloids [107] [88] shows strong concordance in symptomatic relief claimed.…”
Section: History Of Medicinalmentioning
confidence: 99%